Philosophers of the World Unite! Theorising Digital Labour and Virtual Work - Definitions, Dimensions and Forms. (2014) - Sandoval, Edited by Marisol; Fuchs, Christian; Prodnik, Jernej A.; Sevignani, Sebastian; Allmer, Thomas
No abstract available